Methodological bases of knowledge ofessence andspectfity of music in scientific creativity B. Asafiev - Smirnova, L.O.; Kozina, T.M. (Pedagogy of Higher and Secondary Education, 2006)
Clause is devoted to questions of logic communication intonational "the theories of a history" B. Astaffiev and his rules musical of didactis. which have continuation and recognition in modem worts musicologists of Ukraine and outside of her.